Effects of Processing and Storage Preservation Technologies on Nutritional Quality and Biological Activities of Edible Fungi: A Review. Issue 3 (30th June 2016) - Xue, Zhaohui; Hao, Jingfeng; Yu, Wancong; Kou, Xiaohong
Abstract: Consumption of edible fungi, which are rich in nutritional and bioactive components, plays an important role in human health. A gradual decline in moisture, sensory properties, quality of edible fungi is observed after harvest. The recent studies on the changes of nutritional quality and biological activities of edible fungi during processing and postharvest storage have been summarized in this review. In addition, the study discusses the recycling of waster that is produced in processing. The action of bioactive components and their proposed mechanisms of action have also been discussed to accelerate the further exploration and utilization of edible fungi. Practical Applications: Nutritional contents and bioactive components of edible fungi have a direct dependence on the type of processing and storage preservation technique used, which influences the chemical composition and commercial value of edible fungi. Therefore, the aim of this review is to summarize the information described to date about the effects of processing and storage on edible fungi, to give further detailed guidance for obtaining a technological and economic alternative for use with edible fungi, with special emphasis on the various mechanisms potentially involved. It is clear that further scientific studies need incorporate these technologies into the value‐added edible fungi and edible fungi‐related products.